JAN PAWEł II W JURYSPRUDENCJI AMERYKAŃSKIEJ. PRZEGLĄD PROBLEMATYKI - Motyka, Krzysztof (Wydział Prawa i Administracji UAM, 2004)
The paper is intended as a bibliographical and introductory essay on the reception of John Paul II’s teaching in American legal scholarship. It is based on research into articles published in American legal periodicals over the past 25 years of the current Pontificate, most of which are available in Lexis-Nexis. The research, conducted in November 2003, has identified over 750 entries of „John Paul II” in law reviews and over 150 in legal news, but a great majority of them refer to the Pope merely incidentally, usually in footnotes. The author attributes this fact to the prevailing opinion in legal academia that there is no room for references to religious authorities in legal discourse and - specifically - to the secularization of American legal education, including that provided by religiously affiliated law schools.
JOHN PAUL II IN AMERICAN JURISPRUDENCE. A SURVEY OF ISSUES